ANALISIS PERSEPSI KONSUMEN TERHADAP KUALITAS PELAYANAN PADA PT. GARUDA INDONESIA CABANG BIMA - Sri Ernawati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
The purpose of this study is to analyze and know how the consumer perceptions of service quality at PT. Garuda Indonesia Branch of Bima. This research was conducted at PT. Garuda Indonesia Branch of Bima, The use of method in this research is using Descriptive Research. The time of this research start from March to April 2015, with a total sample of 50 people and sampling method using incidental sampling technique. The results of research known that consumer perceptions of service quality at PT. Garuda Indonesia Branch of Bima seen from the value of t-count in comparison with the t-table value, then obtained t-count is greater than at (t-table 4.463> t-table 1.66) so based on the provisions Hypothesis that states